The Effect of Work Discipline on Employee Performance at the Regional Disaster Management Agency (BPBD) of Pekanbaru City - Ade Nanda Febrian Siregar; Annisa Meliana; Okta Rizal Karsih; Fharisa Nabila Rizvi; Ronal Kurniawan (South East Asian Management Concern, 2026)
Human resources play a crucial role in realizing the company's established vision, mission, and objectives, and can significantly determine the company's actual achievements, given the available resources. Work discipline plays a crucial role in realizing the company's established vision, mission, and objectives, and can significantly determine the company's actual achievements given the available resources. The work discipline instilled by an organization or company in its employees greatly influences employees' dedication to their work. Employee performance is the tangible behavior of each individual regarding the results of their work for the company, so that each employee's work results differ from those of others. An individual's performance, whether good or poor, will significantly impact an organization's ability to achieve its goals. High performance fosters greater employee loyalty to the organization, increases motivation, and allows employees to enjoy the work they perform; however, it can sometimes leave individuals unable to escape the pressures of their work.  The research method employed uses questionnaires or interviews for data collection; thus, the data sources are referred to as respondents. Work discipline has a positive and significant influence on employee performance at the Regional Disaster Management Agency (BPBD) office in Pekanbaru City, as evidenced by the t-test, which indicates that the calculated t-value is greater than the critical t-value (7.038).